2007
DOI: 10.1007/s10535-007-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of endogenous contents of phytohormones during internode development in Merremia emarginata

Abstract: During the entire period of internode growth of Merremia emarginata contents of gibberellic acid (GA 3 ), phenyl-acetic acid (PAA), indole-3-acetic acid (IAA, free and conjugated) and abscisic acid (ABA, free and conjugated) were estimated by ELISA using polyclonal antibodies raised against each hormones. At the time of internode elongation free auxin content was low and increased with the decrease in the rate of elongation. In contrast, conjugated IAA showed declining trend where free IAA content was remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…There was an accumulation of radioactivity in the retention time equivalent to auxin conjugates ( Fig 1A). This result is in agreement with the fact that 90 % of the endogenous auxin is normally found in the conjugate form (Normanly et al 1995), although with some exceptions (Patel and Thaker 2007). The alkaline hydrolysis of fractions corresponding to the conjugate accumulation and dosage with antibodies specific against IAA make it evident that the regions corresponding to the peaks contain IAA (Fig.…”
Section: Sucrose [%]supporting
confidence: 88%
“…There was an accumulation of radioactivity in the retention time equivalent to auxin conjugates ( Fig 1A). This result is in agreement with the fact that 90 % of the endogenous auxin is normally found in the conjugate form (Normanly et al 1995), although with some exceptions (Patel and Thaker 2007). The alkaline hydrolysis of fractions corresponding to the conjugate accumulation and dosage with antibodies specific against IAA make it evident that the regions corresponding to the peaks contain IAA (Fig.…”
Section: Sucrose [%]supporting
confidence: 88%
“…Several studies revealed the differential expression of phytohormones especially GA and ABA during seed germination and growth of seedlings. ABA was found to be lower during seed germination stage and early seedling developmental stages and negatively correlated with seed filling 43 and elongation of internodes 44 , however, ABA increases when the growth of the plant ceases 43 . GA was positively correlated with elongation during internodal development 44 .…”
Section: Discussionmentioning
confidence: 90%
“…ABA was found to be lower during seed germination stage and early seedling developmental stages and negatively correlated with seed filling 43 and elongation of internodes 44 , however, ABA increases when the growth of the plant ceases 43 . GA was positively correlated with elongation during internodal development 44 . Different phytohormones including GA and ABA are responsible for the differential response of the plant to light and darkness 45 .…”
Section: Discussionmentioning
confidence: 90%